SERUM FERRITIN AND SERUM LACTATE DEHYDROGENASE LEVELS AMONG COVID-19 PATIENTS - KAPARUWAN, ASTHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of this study was to estimate serum ferritin and serum lactate dehydrogenase (LDH) values among COVID-19-positive and COVID-19-negative subjects. Methods: The study was conducted on 152 cases; 76 were COVID-19 diseased, and 76 were COVID-19 free. Serum ferritin and serum LDH levels were estimated. Result: Average ferritin levels among COVID-19 diseased were 529.33 ng/ml compared to 450.92 ng/ml among negative individuals. Similarly, the LDH level among positive persons was 338.50 IU/L and 303.30 IU/L among hostile people. Conclusion: The uncontrolled and dysfunctional immune response is connected with macrophage activation and hyperferritinemic syndrome. Elevated LDH readings seem to reflect that multiple organ injury and failure may play a more prominent role in influencing the clinical outcomes in patients with COVID-19.